Templateless, Plating‐Free Fabrication of Flexible Transparent Electrodes with Embedded Silver Mesh by Electric‐Field‐Driven Microscale 3D Printing and Hybrid Hot Embossing - Zhu, Xiaoyang; Liu, Mingyang; Qi, Ximeng; Li, Hongke; Zhang, Yuan‐Fang; Li, Zhenghao; Peng, Zilong; Yang, Jianjun; Qian, Lei; Xu, Quan; Gou, Nairui; He, Jiankang; et al. (Advanced materials (Weinheim), 2021)
Flexible transparent electrodes (FTEs) with an embedded metal mesh are considered a promising alternative to traditional indium tin oxide (ITO) due to their excellent photoelectric performance, surface roughness, and mechanical and environmental stability. However, great challenges remain for achieving simple, cost‐effective, and environmentally friendly manufacturing of high‐performance FTEs with embedded metal mesh. Herein, a maskless, templateless, and plating‐free fabrication technique is proposed for FTEs with embedded silver mesh by combining an electric‐field‐driven (EFD) microscale 3D printing technique and a newly developed hybrid hot‐embossing process. The final fabricated FTE exhibits superior optoelectronic properties with a transmittance of 85.79%, a sheet resistance of 0.75 Ω sq−1, a smooth surface of silver mesh (Ra ≈ 18.8 nm) without any polishing treatment, and remarkable mechanical stability and environmental adaptability with a negligible increase in sheet resistance under diverse cyclic tests and harsh working conditions (1000 bending cycles, 80 adhesion tests, 120 scratch tests, 100 min ultrasonic test, and 72 h chemical attack). The practical viability of this FTE is successfully demonstrated with a flexible transparent heater applied to deicing. The technique proposed offers a promising fabrication strategy with a cost‐effective and environmentally friendly process for high‐performance FTE. A maskless, templateless, and plating‐free fabrication method for high‐performance flexible transparent electrodes with embedded silver mesh is proposed by combining an electric‐field‐driven microscale 3D printing technique and a hybrid hot‐embossing process. The flexible transparent electrode with embedded silver mesh exhibits excellent photoelectric properties, remarkable mechanical stability, and environmental adaptability.